The use of YouTube videos to enhance students’ pronunciation accuracy - Ratna Widya Iswara; Silvia Catalan Ambag; Nur Ifadloh (Early Publishing Group, 2025)
This study addresses the critical role of pronunciation in effective English communication, emphasizing the need for innovative and engaging instructional methods beyond traditional drills. While existing research highlights the benefits of digital media, particularly YouTube, for language learning, there remains limited understanding of how learners actively engage with YouTube content specifically for pronunciation improvement. Current studies often focus on performance outcomes or general attitudes, neglecting detailed insights into learners’ strategies and perceptions during their interaction with such media. This research aims to explore how students utilize YouTube videos to enhance their pronunciation accuracy, emphasizing learner autonomy and active engagement. Employing a qualitative, case study design, the study involved 15 undergraduate students enrolled in an English language education program at a university in Indonesia. Data were collected through semi-structured interviews and reflective learning journals over a six-week period, allowing participants to document their experiences, usage patterns, and perceived progress. Thematic analysis was used to interpret the data, facilitating an in-depth understanding of the strategies and cognitive processes involved. Key findings reveal that students actively employ various self-directed techniques such as repetition, shadowing, mimicry, and the use of subtitles to improve pronunciation. They engage multisensorily by combining visual, auditory, and reflective strategies, which foster autonomous learning and motivation. The study underscores the importance of integrating YouTube in pronunciation teaching to promote learner-centered approaches and enhance phonological awareness. The implications suggest that language educators should guide students in effective digital strategies and incorporate multimedia resources into their pedagogical practices. Overall, this research contributes to the understanding of learner engagement with digital media and offers practical insights for optimizing pronunciation instruction using YouTube.